Participatory land use planning in Buvuma Town Council subcounty- Empowering communities for sustainable development - Nangendo, G.; Kyasiimire, B.; Opige, M.; Ssemmanda, R. (Ecological Trends Alliance Texts, 2021)
Of the 4429 hectares administrated by Buvuma Town Council subcounty, Uganda, 30% was assigned to oil palm cultivation, with 21% declared as protected forests. This leaves local communities with hard choices about how to meet their needs from the remaining 49% of land. Ecological Trends Alliance, supported by Tropenbos International, worked with the five parishes that make up Buvuma Town Council to achieve food security and sustainable land management through a new land use plan. This was developed through dialogue and participatory processes with communities in each parish to ensure that the plan promoted inclusive decision making and monitoring. This infobrief presents the vision, goal and objectives identified by communities to move the subcounty towards more sustainable land use, and outlines the main issues and recommendations toaddress these challenges.